2018
DOI: 10.1126/science.aar8238
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted carbonyl-olefin metathesis via oxygen atom transfer

Abstract: Some of the simplest and most powerful carbon-carbon bond forming strategies take advantage of readily accessible ubiquitous motifs: carbonyls and olefins. Here we report a fundamentally distinct mode of reactivity between carbonyls and olefins that differs from established acid-catalyzed carbonyl-ene, Prins, and carbonyl-olefin metathesis reaction paths. A range of epsilon, zeta-unsaturated ketones undergo Brønsted acid–catalyzed intramolecular cyclization to provide tetrahydrofluorene products via the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 60 publications
2
67
0
Order By: Relevance
“…6a,6f Only those that provide extended aromatic products (2) proceed in comparably high yields to their 5-membered homologs. 6b, [10][11][12] Furthermore, competing Lewis acid-catalyzed carbonyl-ene reactions have proven challenging to control and result in diminished yields of the desired metathesis products. Our recent efforts aimed at ex- panding the scope of carbonyl-olefin metathesis reactions have shown that FeCl3 monomers (6) can associate in situ 13 to form Lewis acidic superelectrophiles 14 (7).…”
Section: Introductionmentioning
confidence: 99%
“…6a,6f Only those that provide extended aromatic products (2) proceed in comparably high yields to their 5-membered homologs. 6b, [10][11][12] Furthermore, competing Lewis acid-catalyzed carbonyl-ene reactions have proven challenging to control and result in diminished yields of the desired metathesis products. Our recent efforts aimed at ex- panding the scope of carbonyl-olefin metathesis reactions have shown that FeCl3 monomers (6) can associate in situ 13 to form Lewis acidic superelectrophiles 14 (7).…”
Section: Introductionmentioning
confidence: 99%
“…6a,6f Only those that provide extended aromatic products (2) proceed in comparably high yields to their 5-membered homologs. 6b, [10][11][12] Furthermore, competing Lewis acid-catalyzed carbonyl-ene reactions have proven challenging to control and result in diminished yields of the desired metathesis products. Our recent efforts aimed at ex- panding the scope of carbonyl-olefin metathesis reactions have shown that FeCl3 monomers (6) can associate in situ 13 to form Lewis acidic superelectrophiles 14 (7).…”
Section: Introductionmentioning
confidence: 99%
“…3) Recent investigations of Brønsted acid-catalyzed oxygen atom transfer reactions have shown that alternate oxetane fragmentation pathways exist competing with carbonyl-olefin metathesis reactions. 9 Specifically, acidic protons in the α-position to the carbonyl functionality can engage in distinct oxetane fragmentation pathways under acid-catalyzed conditions forming the corresponding unsaturated alcohols 10 via elimination ( Fig. 2C).…”
Section: Introductionmentioning
confidence: 99%